(untitled) (Research, Society and Development, 2024)
The following study aims to identify the contributions of literature on the role of the nurse in promoting adolescent health. It is an integrative literature review, conducted from February to May 2024. Data collection resulted in 364 articles, with 31 articles in the LILACS database, 291 in MEDLINE, and 42 in BDENF. Out of this total, 354 articles were excluded as they did not meet the previously established inclusion and exclusion criteria. Thus, in the present integrative review, 10 articles were analyzed, which presented various methodological approaches, published between 2018 and 2023. Many of the studies highlight the potential of nurses in adolescent health, focusing on educational activities, assessments, promotion of physical exercises, and prevention of sedentary behavior. The use of the Event History Calendar (EHC) facilitates communication between nurses and adolescents. However, challenges such as limited understanding of adolescents’ history, restricted knowledge of guidelines, and neglect in health actions persist. Additionally, there is a narrow view of adolescent sexuality among healthcare professionals, with little representation in research on the completeness of this age group. Therefore, the analyzed studies reveal common challenges: nurses have a crucial role in adolescent health, but face difficulties in their practice. It is urgent, therefore, to integrate them more effectively into educational and public health settings.